Monitoring Water Quality and Ecosystem Health Using Copernicus Sentinel Data: Case Studies from Urban and Rural Areas - Putuhena, Jusmy D. (Arbain Publishing, 2024)
The increasing demand for effective water quality monitoring has driven the need for advanced technologies that can provide accurate, real-time insights into ecosystem health. This study explores the use of Copernicus Sentinel data for monitoring water quality and ecosystem health, focusing on case studies from both urban and rural areas. Sentinel satellites, with their multi-spectral imaging capabilities, offer a powerful tool for assessing key water quality indicators such as turbidity, chlorophyll concentration, and surface temperature. By comparing data across diverse environments, the study highlights how urbanization, agricultural activities, and natural phenomena contribute to the degradation of water quality. The findings demonstrate that Sentinel data can be crucial in detecting early signs of ecosystem stress, enabling timely interventions to mitigate environmental risks. The study also discusses the challenges in applying remote sensing technologies in complex environments and emphasizes the importance of integrating satellite data with on-ground measurements for comprehensive ecosystem management. This research provides a foundation for expanding the use of satellite data in environmental monitoring, particularly for policymakers and environmental agencies tasked with managing water resources.